Teaching Biblical Studies Online. - Delamarter, Stephen; Gravett, Sandra L.; Ulrich, Daniel W.; Nysse, Richard W.; Polaski, Sandra Hack (Teaching Theology & Religion, 2011)
In this edited transcript of a panel at the Society of Biblical Literature (November 23, 2009, Boston, Massachusetts), five Bible scholars give brief presentations on various challenges and opportunities encountered when teaching academic biblical studies courses online in both undergraduate and theological education contexts. Each presentation is followed by questions from the audience and discussion. Topics include: a typology of different approaches to online teaching, advantages and disadvantages of online compared to face-to-face classrooms (for both students and faculty), opportunities for imaginative exercises online, the advantages of online threaded discussions, and the joys and pitfalls of bringing your course into an online environment for the first time.